P82 Induced sputum is a feasible diagnostic tool in children with chronic cough possibly due to asthma. (14th November 2013) - Gorman, EA; Bell, J; Murray, J; McCaughey, J; O'Donoghue, D; Shields, MD
Abstract : Background: Chronic cough is a common childhood symptom, reported in 22% of preschool children. Many are misdiagnosed as asthmatic. Induced sputum (IS) using hypertonic saline (HTS) has been used as a diagnostic tool in patients with cough; its bronchoconstriction effects being used as a test for the bronchial hyper-reactivity (BHR) in asthma (ISSAC study). Conversely it is used as a bronchodilator in the treatment of bronchiolitis and pre-school wheeze. Sputum eosinophilia indicates airway inflammation in keeping with a diagnosis of asthma. This study aimed to determine if IS is a feasible diagnostic tool in children with problem cough query asthma. In addition we wished to determine the relationship between BHR to HTS and the eosinophil count in sputum. Methods: A retrospective review of children with problem cough who underwent sputum induction with nebulised 3% HTS. Sputum samples were obtained for microbiology, virology and differential cell count. Spirometry was performed before and after administration of 3% HTS. Change in FEV1 (Δ FEV1 = FEV1 post HTS minus FEV1 pre HTS) was used as a measure of BHR. Correlation between Δ FEV1 and sputum eosinophilia was calculated using Spearmen rank coefficient. Results: 146 patients referred for IS between 2001 and January 2013 were included. Mean age = 8 years (range = 2 to 13), mean cough duration = 4.25 years (range 0.17 to 11.5). Sputum induction was successful in 131 patients (89%). 12 children (8%) became symptomatic; 4% required test termination. 44 children increased FEV1 with 12 having >9% FEV1 increase. 63 children reduced FEV1 with 21 having > 9% reduction. Viral or bacterial pathogens were identified in 29% of samples obtained. Sputum eosinophilia (eosinophil count > 3%) was present in 66% of samples obtained. There was no correlation between FEV1 and sputum eosinophilia (R = 0.04). Conclusions: IS is a feasible and safe tool in children with problem chronic cough, aiding diagnosis with spirometry and sputum analysis. However BHR induced with HTS does not correlate with sputum eosinophilia. Several children increased FEV1 with HTS administration, suggesting it may have a therapeutic role in the treatment of some children with chronic cough.